Longwall top coal caving design for thick coal seam in very poor strength surrounding strata - Jangara, Hossein; Ozturk, C.A. (Springer Science and Business Media LLC, 2020)
Abstract Alpu lignite field is an important coal deposit with nearly 2 billion tons of coal resources located in the middle of Turkey. The mine deposit consists of three main seams. The thickness of two of them vary from 4 to 30 m. The surrounding rock mass is very poor in terms of strength. The high clay content and weak rock mass make mechanized mining difficult. In this research, applicability of the longwall top coal caving method was investigated. The very weak strength behavior of the coal and the surrounding strata increases the importance of research in the mine site in terms of ground control. The aim is to design the mechanized longwall mine based on ground control principles. First of all, classification of the roof, coal, inter-burden, and floor strata were classified based on geotechnical aspects. Then, cavability index, shield, and floor bearing capacity were investigated. Different methods were applied to understand the limitations of a mechanized system that is very critical due to the very low strength strata. According to the main results, roof strata was classified as immediately caving while mining height was calculated as 5–6 m. Finally, the relations among geotechnical characterizations of roof and floor strata, cutting and caving heights, and required shield capacity were presented based on analytical and numerical applications. The proposed approach can be used as a ground control method for the applicability as well as the limitations of mechanized longwall mining design in weak strata conditions.
Keywords: Roof; Rock mass classification; Mining engineering; Engineering; Civil engineering; Safety, Risk, Reliability and Quality; Waste management; Civil and Structural Engineering; Petrology; Coal mining; Longwall mining; Geology; FOS: Earth and related environmental sciences; Rock Mechanics and Engineering; Geotechnical engineering; Coal; Mechanics of Materials; Physical Sciences; Shield; Factors of Safety and Reliability in Geotechnical Engineering; rock cutting; Prediction of Tunnel Boring Machine Performance; FOS: Civil engineering